Current state of guidance and counseling in secondary schools in Zimbabwe - Gudyanga, Ephias; Wadesango, N.; Manzira, L. R.; Gudyanga, Anna (Kamla-Raj, 2016)
Key players in the education system such as District Education Officers, head teachers and teachers need to improve their performance in order to effectively implement the guidance and counseling curriculum in Zimbabwe. All key players should work hard in fulfilling their job descriptions. The aim of this desktop study was to review literature in order to ascertain the current state of guidance and counseling in schools. Thus the findings from the study will help in restructuring the Zimbabwe secondary schools guidance and counseling services. From the various literature reviewed, it emerged that qualifications and teaching experience had nothing to do with the implementing of Guidance and Counseling. Some of the teachers who are given the responsibility of implementing Guidance and Counseling do not have its general understanding. It is recommended that, if possible, Guidance and Counseling be made an integral part of co-curricular activities and given a place on the school timetable.